63. Phase dependency of the human primary motor cortex and cholinergic inhibition cancellation during beta tACS. Issue 12 (December 2016) - Guerra, A.; Pogosyan, A.; Nowak, M.; Tan, H.; Ferreri, F.; Di Lazzaro, V.; Brown, P.
Abstract : Growing evidence suggests that human motor cortex has a tendency to resonant activity at about 20 Hz, and therefore stimulation near this frequency can synchronize the activity of neuronal populations. However, do interneuronal circuits contribute to such resonance and if so are they selectively entrained? Is the balance between inhibitory and excitatory interneurons maintained throughout? We investigated how different interneuronal circuits react to exogenously driven rhythmic activities using TMS during transcranial alternating current stimulation (tACS) at motor and non-motor resonance frequencies. We tested different TMS interneuronal protocols and triggered TMS pulses at different phases of tACS. The effect of short-latency afferent inhibition was abolished by tACS at 20 Hz regardless of phase of stimulation. tACS phase selectively modulated MEP size during single pulse, GABAAergic short-interval intracortical inhibition (SICI), and glutamatergic intracortical facilitation (ICF). In the case of ICF and SICI this phase effect was more marked during stimulation at 20 Hz. Moreover, the phase dependency of ICF and SICI was relatively balanced so that net effects on cortical excitability were attenuated. The present study provides in vivo evidence linking cortical beta activity to sensorimotor integration, and for dynamic but balanced glutamatergic and GABAAergic effects during beta oscillations in motor cortex.